2016
DOI: 10.1016/j.midw.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

First-time mothers’ experiences of early labour in Italian maternity care services

Abstract: Objective. To explore first-time mothers' experiences of early labour within Italian maternity care services in the event that women are admitted to hospital or advised to return home after maternity triage assessment. Setting. One second-level Maternity Hospital in northern Italy with an obstetric unit for both low and high-risk women. Participants. Fifteen first-time mothers in good general health with spontaneous labour at term of a low-risk pregnancy that accessed the maternity triage during the latent pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…The present study found that women with a prolonged latent phase regardless of parity are dominating the group of women being admitted at earlier stages of cervical dilatation. According to the findings from Ängeby et al and Cappelleti et al, women with a prolonged latent phase wanted individually adapted care but not necessarily admittance to the labor ward. In Sweden, as in many other countries, women have no options for a home visit from a midwife during the latent phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study found that women with a prolonged latent phase regardless of parity are dominating the group of women being admitted at earlier stages of cervical dilatation. According to the findings from Ängeby et al and Cappelleti et al, women with a prolonged latent phase wanted individually adapted care but not necessarily admittance to the labor ward. In Sweden, as in many other countries, women have no options for a home visit from a midwife during the latent phase.…”
Section: Discussionmentioning
confidence: 99%
“…Marowitz suggested that midwives can provide a significant amount of individually adapted care and support in early labor in order to delay admission, but a tension exits between delaying admission and women's difficulty in handling early labor at home. Previous studies show that individual midwifery support for women during latent phase is important. Paul et al's suggestion of an early labor lounge to engage women in labor‐promoting activities as a potential approach in lowering the cesarean birth rate in nulliparous women may be a promising strategy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Cappelletti et al (2016) reported on the increasing role of technology on early labour management and experiences of women giving birth for the first time, with a range of apps now available to enable women to count the frequency and duration of their contractions. Other devices, including wearable abdominal monitors are also now being advertised which purport to enable women to distinguish between a contraction and abdominal cramps.…”
Section: Women's Use Of Technologymentioning
confidence: 99%
“…Despite agreement from maternity care providers, research evidence and international guidelines (1)(9) on the benefits of delaying hospitalization during the latent phase, childbearing women often manifest the need for reassurance and support during early labour and may expect to be admitted to hospital, even if not in active labour (19) (20) (21). Therefore, the latent phase of labour is recognized as an area of conflict between women and healthcare professionals (22).…”
Section: Introductionmentioning
confidence: 99%